“The advice? Think bigger”: Community perspectives on dairy farming, including surplus calves—An Australian focus group study - Sarah E. Bolton; Bianca Vandresen; Marina A.G. von Keyserlingk (Journal of Dairy Science)
ABSTRACT: Citizens are becoming increasingly disconnected from food production. Despite this, many people still hold strong values about how food is produced. The aim of this study was to attain an in-depth understanding of Australian public attitudes toward sustainability and animal welfare in dairy production, as well as early-life killing of surplus dairy calves and cow-calf separation, issues commonly identified as being out of step with public values. We conducted 3 focus group sessions, each with 8 Australians who varied in age, gender identity, income, and frequency of consumption of dairy products. Thematic analysis of the semistructured discussions resulted in 2 key themes, each with underlying subthemes: (1) animal agriculture as an industry, including sustainability, farmers as people, and farming practices; and (2) personal impacts and reflections as citizens, including ethical considerations, and consumer behaviors. Participants varied in their attitudes toward sustainability and the consumption of animal products. This variation was influenced by the different ethical lenses through which they viewed the topics and alignment or otherwise with their personal values. Many participants acknowledged that farmers have a hard life and care about their animals but must also prioritize economics when making management decisions. Most participants were unaware of the common dairy industry practices of early-life killing of surplus calves and cow-calf separation, but once made aware, there was widespread rejection of the practices. Understanding and correcting where food animal production practices fail to align with the evolving values of the public provides opportunities to preserve the social sustainability of animal agriculture into the future.